Polysaccharide-based emulsion gels as fat replacers in Frankfurter sausages: Physicochemical, nutritional and sensorial evaluation. (15th April 2023) - Fontes-Candia, Cynthia; Martínez-Sanz, Marta; Gómez-Cortés, Pilar; Calvo, María Visitación; Verdú, Samuel; Grau, Raúl; López-Rubio, Amparo
Abstract: Agar and κ-carrageenan emulsion gels were used to produce Frankfurters with reduced animal fat content by partially (50%) or completely (100%) replacing the pork back fat. The results showed that 50% of the pork back fat substitution did not affect the mechanical and physicochemical properties of the obtained sausages compared with the control (pure pork back fat). Slight changes in the textural and TBARS values were observed for the 100% substituted sausages, while a reduction from 25.37 to 17.07 g/g sample of total fat was attained. Thus, decreasing the caloric content from 280 to 209 kcal/g sample. The saturated fatty acid/unsaturated fatty acid ratio was also reduced from 0.58 to 0.38 with 50% substitution and 0.17 with total substitution, thus diminishing the atherogenic and thrombogenic indexes by 35% and 70%, respectively. The reformulated Frankfurters with a reduced-fat content were accepted by the consumers, evidencing that the polysaccharide-based emulsion gels can be promising ingredients for developing meat products with improved nutritional composition. Highlights: Agar and κ-carrageenan emulsion gels are potential pork back fat replacers in Frankfurters. Improved lipid profile was seen in the reformulated Frankfurters. Textural and sensorial properties were affected by the percentage of substitution. Healthier Frankfurters with a reduced-fat content were accepted by the consumers.